2008
DOI: 10.1038/leu.2008.84
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib induces durable cytogenetic responses in patients with chronic myelogenous leukemia in chronic phase with resistance or intolerance to imatinib

Abstract: Dasatinib, a potent inhibitor of BCR-ABL in vitro, is effective for patients with chronic myelogenous leukemia (CML) resistant or intolerant to imatinib. To provide a more definitive assessment of dasatinib in chronic-phase (CP)-CML, we report extended follow-up of a phase II trial, presenting data for the entire patient cohort (N=387). Dasatinib (70 mg) twice daily was administered to patients with imatinib-resistant or -intolerant CP-CML. With median follow-up of 15.2 months (treatment duration, <1-18.4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
235
1
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(258 citation statements)
references
References 20 publications
9
235
1
13
Order By: Relevance
“…70 Dasatinib also was associated with grade 3/4 nonhematologic AEs, including pleural effusion in 6% of patients. 70 To minimize dasatinib-related toxicity while maintaining efficacy, a dose-optimization study was initiated.…”
Section: Dasatinibmentioning
confidence: 99%
See 2 more Smart Citations
“…70 Dasatinib also was associated with grade 3/4 nonhematologic AEs, including pleural effusion in 6% of patients. 70 To minimize dasatinib-related toxicity while maintaining efficacy, a dose-optimization study was initiated.…”
Section: Dasatinibmentioning
confidence: 99%
“…70 Dasatinib also was associated with grade 3/4 nonhematologic AEs, including pleural effusion in 6% of patients. 70 To minimize dasatinib-related toxicity while maintaining efficacy, a dose-optimization study was initiated. 74 In that phase 3 trial, 670 patients with imatinib-resistant or imatinib-intolerant CML-CP were randomized to receive 1 of 4 doses of dasatinib: 100 mg once daily, 50 mg twice daily, 140 mg once daily, or 70 mg twice daily.…”
Section: Dasatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…112 When grouped together, the presence or absence of an Abl kinase mutation did not appear to influence the rates of CHR or MCyR in imatinib-resistant patients receiving dasatinib in the previously published START trials. 36,105 However, specific mutations appear to be differentially resistant to dasatinib both in vitro, as well as in vivo. Jabbour and colleagues also recently demonstrated equivalent response rates to second-generation TKIs when imatinib-resistant patients were grouped according to the presence or absence of a mutation.…”
Section: Second-generation Kinase Inhibitorsmentioning
confidence: 99%
“…36 The START-C trial also evaluated dasatinib in 288 imatinib-resistant patients, and demonstrated that 85% of patients had achieved a new CHR, 51% obtained a new MCyR and 40% had achieved a new CCyR, corroborating the results from the START-R trial. 105 Nilotinib has also been evaluated in several trials for patients with imatinib-resistant CP-CML. Kantarjian and colleagues 106 reported on approximately 220 imatinib-resistant CP-CML patients receiving nilotinib 400 mg twice daily, and after a median follow-up of 19 months, 56% achieved a McyR, whereas 41% obtained a CCyR.…”
Section: Second-generation Kinase Inhibitorsmentioning
confidence: 99%